Business & Regulatory Impact Assessment (BRIA) results : Job Start Payment : The Scotland Act 1998 (Transfer of Functions to the Scottish Ministers etc.) Order 2020.: Job Start Payment : The Scotland Act 1998 (Transfer of Functions to the Scottish Ministers etc.) Order 2020. (2020) - Unknown
No abstract available